THE INTEGRATION OF ICT IN FOREIGN LANGUAGE TEACHING: STRATEGIES FOR IMPROVING LEARNER ENGAGEMENT - Allaniyazova, Khilola (International Conference on Science, Education & Law, 2025)
This paper examines the role of Information and Communication Technologies (ICT) in enhancing learner engagement and motivation in foreign language teaching. The integration of ICT into the educational process has reshaped traditional teaching methods, transforming them into more interactive, personalized, and learner-centered experiences. Drawing on recent pedagogical studies and practical examples, this research discusses the benefits, challenges, and strategies for effective ICT implementation in language classrooms, with a focus on fostering communication, creativity, and autonomy among learners.